Development of Social Skills with Traditional Games: An Experimentation with the Game Mallogo - Tasnim, Aeni; Damayanti, Eka; Afiif, Ahmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aims to prove the improvement of social development through the traditional game of mallogo for children aged 5-6 years at Ponre, Gantarang, Bulukumba.Design/methods/approach – This study is a quantitative research using experimental methods. The research design used is a one-group pretest-posttest design. The population in this study are 8 children aged 5-6 years who live in Ponre, Gantarang, Bulukumba and whole child are sample in this research. The data collected throught developmental assessment using observation base on children age 5-6 social and emotional development indicators was set by Minister of Education and Culture No. 137 of 2014 concering National Standard for Early Childhood Education. The data analysis technique used is Wilcoxon’s non-parametric statistic test.Findings – The results of this study are that the average value of the pre-test was 25,625, while the average value of the post-test was 54.875. Wilcoxon test obtained the calculated value of -2.52 Zcount, which is smaller than the value of Ztable of -1.96, which was carried out with a two-tailed test (-2.52 < -1.96). The results show an increase in social development through traditional mallogo games for children aged 5-6 years at Ponre, Gantarang, Bulukumba.Research implications/limitations – This study has implications for developing traditional games in children’s social skills. In the future, the number of participants needs to be increased. Parametric statistical tests are needed to strengthen the research results.Practical implications – This study has practical implications for experimental studies of children’s social abilities.Originality/value – This study contributes to the development of the study of children’s play. In addition, this research provides a new perspective on children’s social development through the traditional game method. Paper type: Research paper